Human Capital Development in Education and Economic Growth: A Granger Causality Test in Pre- and Post-Deregulated Nigerian Economy (1970-2011) - Olusanya, Samuel Olumuyiwa (West African Journal of Open and Flexible Learning, 2013)
The research paper investigated the impact of human capital development in education and economic growth in the pre-and post-deregulated Nigerian economy. The paper employed secondary data and the Granger causality test was adopted as the estimation technique between 1980 and 2011. Data from Human Capital Development in Education (HCDE) and Gross Domestic Product (a proxy for economic growth) were subjected to an empirical analysis using the Granger causality test. The results revealed that human capital development in education caused economic growth in the pre-deregulated Nigerian economy but during the deregulation period, human capital development in education caused economic growth. Similarly, human capital development in education did not cause economic growth in the post-deregulated Nigerian economy. Therefore, the study recommended that the Nigerian Government should invest more in human capital development in the education sector to meet the goal of Vision 2020 and should be more involved in raising the standard of education in the country. Finally, Nigeria can only reposition herself as a potent force through the quality of her products from the primary, secondary, and tertiary school systems as well as making her manpower relevant in the highly competitive and globalised economy through a structured and strategic planning of her educational institutions.
Keywords: Human capital development; economic growth; education, productivity; Vision 2020; education